First isolation, identification, and pathogenicity evaluation of an EV-G6 strain in China - Zhu, Pei; Li, Zhan-Hong; Li, Zhuo-Ran; Zhang, Zhen-Xing; Song, Jian-Ling (Frontiers in Veterinary Science, 2024)
Enterovirus G (EV-G) belongs to the Picornaviridae family and infects porcine populations worldwide. A total of 20 EV-G genotypes (EV-G1 to EV-G20) have been identified. In this study, we isolated and characterized an EV-G strain, named EV-G/YN29/2022, from the feces of diarrheic pigs. This was the first EV-G6 strain isolated in China. Comparison of the whole genome nucleotide and corresponding amino acid sequences showed that the isolate was more closely related to those of the EV-G6 genotype than other genotypes, with the complete genome sequence similarity ranging from 83.7% (Iba46442) to 84.4% (PEV-B-KOR), and corresponding amino acid homology ranged from 96% (Iba46442) to 96.8% (PEV-B-KOR). Similarly, the VP1 gene and corresponding amino acid sequences of EV-G/YN29/2022 were highly similar to those of the EV-G6 genotype (>82.9% and >94.3%, respectively). Thus, the isolated strain was classified as EV-G6 genotype. This was the first EV-G6 strain isolated in China. Pathogenicity analyses revealed that EV-G/YN29/2022 infection caused mild diarrhea, typical skin lesions, and weight reduction. The strain was mainly distributed to the intestinal tissue but was also found in the brain, mesenteric lymph nodes, spleen, and liver. Our results can be used as a reference to further elucidate the epidemiology, evolution, and pathogenicity of EV-G.